1997
DOI: 10.1161/01.cir.95.2.363
|View full text |Cite
|
Sign up to set email alerts
|

Serial Follow-up After Optimized Ultrasound-Guided Deployment of Palmaz-Schatz Stents

Abstract: Serial ultrasound analyses did not show any evidence of stent compression or relevant vessel remodeling. Restenosis was solely due to neointimal ingrowth. Despite a considerable plaque burden within the reference segments, there was no relevant progression of the disease adjacent to the stent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(45 citation statements)
references
References 22 publications
4
41
0
Order By: Relevance
“…Intravascular ultrasound has shown that the stent area remains constant during follow-up and that stents can prevent constrictive vessel remodeling. 20,21 It has been recognized that almost all stent implantations cause some tissue proliferation and neointimal hyperplasia at the stented lesion 22 and this tissue proliferation seems to be associated with genetically controlled ACE activity. 11 The increase in the late loss mainly indicates inward tissue proliferation within stented lesion and the progression of this inward remodeling in patients with the DD genotype may be associated with the higher ACE activity.…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular ultrasound has shown that the stent area remains constant during follow-up and that stents can prevent constrictive vessel remodeling. 20,21 It has been recognized that almost all stent implantations cause some tissue proliferation and neointimal hyperplasia at the stented lesion 22 and this tissue proliferation seems to be associated with genetically controlled ACE activity. 11 The increase in the late loss mainly indicates inward tissue proliferation within stented lesion and the progression of this inward remodeling in patients with the DD genotype may be associated with the higher ACE activity.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Over the past decade, both systemic pharmacological and novel mechanical treatment strategies to prevent in-stent neointimal hyperplasia have been unsuccessful. [3][4][5] Only intracoronary radiation therapy has emerged as a promising modality to attenuate the neointimal hyperplasia after stent placement.…”
mentioning
confidence: 99%
“…In general, a small RVD has been shown to be an independent predictor of in-stent restenosis. 21,[36][37][38] In-stent restenosis is almost entirely due to intimal proliferation 39,40) and the amount of intimal hyperplasia and thus late loss is relatively constant and independent of stent size, 41) and this has been held responsible for the increased rate of restenosis in stented small vessels by Elezi, et al 32) who, in a large series of 2602 stented patients, found small vessel size, DM, previous PTCA, complex lesion morphology, multiple stents, DS before intervention, and a lower balloonto-vessel ratio to be independent predictors of in-stent restenosis. In an analysis by Akiyama, et al 18) baseline RVD, lesion length, and final intrastent cross-sectional area irrespective of vessel size were demonstrated to be independent predictors of in-stent restenosis.…”
Section: Discussionmentioning
confidence: 99%